MENINGKATKAN KETERAMPILAN MENYIMAK DENGAN METODE PEMBELAJARAN READ ALOUD PADA ANAK USIA DINI (5-6 TAHUN) DI TK WACHID HASYIM 2 SURABAYA - ivory HANA hana; Anisa Yunita Sari; Varia Virdania Virdaus (Universitas Narotama, 2023)
MENINGKATKAN KONSENTRASI BELAJAR ANAK DENGAN METODE BERCERITA DI TK AL – IMANImproving listening skills in early childhood (5-6 years old) using a read aloud method at TK Wachid Hasyim 2 Surabaya. The observation occured during learning activities in a story tellig. It seems that when the teacher reads a story, the exprssion, intonation, and the body langauge is not delibeately shown. It cause the children attention to the story is not maximum. The childrn lose the focus and interest to the story. Out of 15 students, only 11 who are able to retell the story that has been rad. On the inteview session, it is found that the teacher had not made efforts to increase the skill of students’ listening skill. In addition, the teacher has not developed learning methods to deliver the story. Researchers used the qualitative method of PTK (Penelitian Tindak Kelas). The PTK model that researchers used in this study was spiral method from the Kemmis Researcher Model (1988). In the book PTK (Rochiati Wiriaatmadja, 2008 : 66) From the first cycle, and II is carried out with the planning stage (plan), action (act), observation (observer) and reflection (reflection). The results of the class research that it can be concluded that improving the listening skills using the read aloud method for early years student (5-6 years) at TK Wachid Hasyim 2 is giving a good impaact. This me`thod can be also use as a` reference for other grades. Keywords: learning method, read aloud, listening skills